2022
DOI: 10.3389/fimmu.2022.950275
|View full text |Cite
|
Sign up to set email alerts
|

In search of immune cellular sources of abnormal cytokines in the blood in autism spectrum disorder: A systematic review of case-control studies

Abstract: Abnormal cytokine levels in circulating blood have been repeatedly reported in autism; however, the underlying cause remains unclear. This systematic review aimed to investigate cytokine levels in peripheral blood compartments and identify their potential immune cellular sources in subjects with autism through comparison with controls. We conducted an electronic database search (PubMed, Scopus, ProQuest Central, Ovid, SAGE Journals, and Wiley Online Library) from inception (no time limits) to July 9, 2020, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 101 publications
1
11
0
Order By: Relevance
“…Alterations in cytokine profiles in children with ASD and notable changes in cytokines and their receptors are highlighted. Key cytokines and their receptors investigated in relation to childhood autism include IL-17 A, IL-1β, IL-2R, IL-4, IL-6, and various interleukins, each with diverse cellular origins and target cell types [ 41 , 42 ]. Consistent with previous studies, our results revealed elevated levels of IL-17 A in children with ASD, indicative of increased inflammation associated with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in cytokine profiles in children with ASD and notable changes in cytokines and their receptors are highlighted. Key cytokines and their receptors investigated in relation to childhood autism include IL-17 A, IL-1β, IL-2R, IL-4, IL-6, and various interleukins, each with diverse cellular origins and target cell types [ 41 , 42 ]. Consistent with previous studies, our results revealed elevated levels of IL-17 A in children with ASD, indicative of increased inflammation associated with ASD.…”
Section: Discussionmentioning
confidence: 99%
“…However, results of the INF-γ levels in ASD from the previous studies were not always consistent. Both higher and lower levels of INF-γ have been found in blood samples and PBMCs of ASD [see the summarized results in the excellent systematic reviews ( 74 , 75 )]. In our clinical practice, we also find that a great heterogenicity exists in the INF-γ levels in ASD.…”
Section: Discussionmentioning
confidence: 99%
“…[36] In addition, we found that the proportions of neutrophils and resting mast cells in patients with ASD. On the one hand, neutrophils can produce a pro-inflammatory cytokine IL-17 [37,38] , which is related to neurodevelopmental disorders. However, an increase in neutrophil oxidative stress leads to a disorder of the enzyme antioxidant network in peripheral innate immune cells.…”
Section: Discussionmentioning
confidence: 99%